Intensity And Effectiveness Of Media Usage Of Othello Props As A Learning Mediation For Mastery Of Operation Concept Build Space In Class V - Dismawati Dismawati (Fakultas Sastra Universitas Ekasakti, 2018)
For subjects whose instructional objectives are more skill-enhancing (psychomotor) such as mathematics subjects, visual aids are indispensable in the learning process. Any abstract concept in mathematics newly understood by a child needs immediate strengthening in order to settle, adhere and long lasting to be embedded in his own mindset and pattern of action (Ruseffendi 2003: 226). For this purpose it is necessary to learn through doing and understanding, not just memorize or remember facts that would be easily forgotten and difficult uniuk owned. As the phrase often expressed by the experts, that: I heard then I forget, I see then I know, I do then I understand. That's why in the teaching of mathematics in elementary school (SD) is still required the use of props. As teachers we need to know the various props that can be used in teaching mathematics subjects, especially in teaching mathematics in elementary. Mathematics subjects on the implementation should be pursued with conducive learning conditions in the sense of an active learning, creative, effective and even innovative. To create a conducive learning condition, there should be an effort to maximize the utilization of existing facilities and infrastructure, even if deemed necessary a teacher can make their own props needed. Mathematics lesson material can not only be conveyed through information or just rely on the formulas, but must be pursued a verification in an effort to avoid verbalism. Othello displays in mathematics lessons conducted at SDN 04 KOTO RANAH Subdistrict IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 can be summarized as follows: In general, student achievement in SDN 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan Regency Year The 2015/2016 lesson prior to the action of beluni reached the optimal level in solving mathematical problems in the broad subject. With props stimulates the liveliness and creativity of learners, it is proven learners Sdn 04 Koto Ranah District IV Nagari Bayang Utara Pesisir Selatan District Lesson Year 2015/2016 during the learning not only silent, but students actively and creatively seek and find a problem the teacher presented. The use of Othello props can have a positive impact on improving students / learner abilities according to the potential of each learner. This is evident in the change in evaluation results that increase from each learner from the first action to the third action.